AN EXAMINATION OF FACTORS ASSOCIATED WITH DELAYED MARRIAGE AMONG YOUTH IN TARAUNI L.G.A., KANO STATE - ISAH KHAMISU MADACHI (International Studies Journal)
In the wake of globalization, technological advancements, and large-scale social change worldwide, youth attitudes and opinions on marriage have undergone transformations due to the multidimensional development of human society, including educational and economic changes. The phenomenon of delayed marriage has become increasingly prevalent among youth in contemporary Nigeria, posing substantial social, cultural, and economic implications. This pressing issue of social concern affects thousands, if not millions, of individuals. In Nigeria, individuals who experience delayed marriage often face ridicule, mockery and individual stigma from relatives and peers. This study investigated the factors contributing to delayed marriage among youth in Tarauni L.G.A., Kano, Nigeria. It explored socio-economic factors, consequences, perceptions surrounding delayed marriage, and potential strategies to reduce its occurrence in the area. The researcher adopted a qualitative research design and employed purposive sampling, selecting eight respondents for in-depth interviews. Thematic summary was used to analyze the data, describing, summarizing, and interpreting it based on the research objectives. The results revealed that various factors contribute to delayed marriage among youth in Tarauni L.G.A., including joblessness, educational pursuits, personal preference and choosiness, particularly among women. This research provides valuable insights into the phenomenon of delayed marriage among youth in Tarauni L.G.A., Kano State. The study confirms the prevalence of delayed marriage, high awareness among the population, and offers a comprehensive understanding of its contributing factors, effects, and potential mitigation strategies.